Big five personality traits and resistance to change among administrative staff in UUM - Balakrishnan, Mageswari (2014)
The aim of this research is investigating the relationship between big five personality traits and resistance to change. Extraversion, agreeableness, conscientiousness, emotional stability and openness to experience are five traits hypothesised to have a significant and negative relationship with resistance to change. Instrument used to obtain the data for this quantitative research paper was a survey questionnaire. A total of 500 survey questionnaires were distributed to the administrative staff in Universiti Utara Malaysia. Of the distribution, only 331 responses have found completed and subsequently analysed for statistical results by using Statistical Package for Social Science (SPSS) version 20.0 software. The two main data analysis techniques: correlation analysis and multiple regression analysis were used to verify the hypotheses. The Pearson correlation analysis confirmed a significant and negative though weak correlation between big five personality traits and resistance to change. By each trait, only emotional stability was found moderately correlated whereas agreeableness and conscientiousness have weak correlation. With analysis of standard multiple regression, a total of 6.3 percent variance of resistance to change was found explained by big five personality traits. As a whole, the findings have indicated that individual personality traits significantly predict resistance to change. ‘How’ an individual perceive change is the key to manage employees’ resistance to organisational change. The findings are believed to help the management practitioners to understand employees’ disposition towards change in order to attain effective change management at the workplace.